Eficiencia de la heliofanía en diferentes tipos de células fotovoltaicas de un sistema aislado en la ESPAM MFL. - Velásquez Delgado, Jessenia Dayanara (2018)
The objective of the research was to evaluate the efficiency of heliophany in different types of photovoltaic cells of an isolated system at ESPAM MFL; the heliophany data was obtained from the ESPAM MFL weather station, the peak sun hours (HSP) were 1.84 and the irradiation obtained by solar map was 2710 W / m2 / day. The daily energy consumption was calculated to be 345 W, the photovoltaic dimensioning of two 50 W panels for each type of isolated, monocrystalline and polycrystalline system, a 10 A charge controller, a 55 Ah battery and an inverter. 500 W. A single-line diagram of the photovoltaic systems consisting of panels, a charge controller, a battery and an inverter was made. The behavior of the voltage and amperage of the photovoltaic systems was analyzed, it was demonstrated that during the first days there was no variation in the voltages, however, in the last days the voltage of the polycrystalline decreased and the monocrystalline increased. As for the amperage, they maintained a constant behavior, obtaining an efficiency of 6.23% monocrystalline and 4.68% polycrystalline. The T-Student test was applied to statistically contrast the results obtained, finding a significant difference of 95%, therefore the hypothesis was accepted because the monocrystalline system had a greater efficiency of solar to electric conversion.